EFFECT OF USE FENUGREEK SEEDS (Trigonella foenum-graecum) ON SOME SEMEN CHARACTERSTICS OF AWASSI RAMS IN WINTER SEASON. - Mohammad Ibrahim (Mesopotamia Journal of Agriculture)
This study aimed to know the effect of three rations contains same crude protein and metabolizable energy but differs in Fenugreek seeds percentage( 0 , 5 and 10 %), Fifteen Awassi rams (2-3 years old), were randomly divided into three equal groups (5 rams/group) weighting 50-55 Kg during winter season from (15/11/2011 - 15/2/2012). Results showed that feeding of Fenugreek seeds had a significant effect (P ≤ 0.05)  on semen ejaculation volume, semen consistency ,mass and individual motility of spermatozoa, percentages of live and dead spermatozoa , sperm abnormality .However there were  no significant effect (P ≤ 0.05) on total sperm  concentration / ml   compared with the control group rams.